Análise custo-efetividade de protocolo clínico para detecção de lesões precursoras do câncer de colo uterino (progyne) - Sousa, Deise Maria do Nascimento (2018)
The objective of this study was to perform the cost-effectiveness analysis of a clinical protocol directed to the gynecological nursing consultation for the prevention of cervical cancer in primary care. It was a research of economic evaluation in health. To carry out the study, the Markov modeling was done through the simulation of a prospective cohort, considering the time horizon of 60 years. The discount rate of 5% was adopted in order to obtain the cost- effectiveness ratio in scenarios with and without cervical cancer screening, taking into account the premises of PROGYNE. The health costs adjusted by the inflation rate of the National Agency for Supplementary Health were estimated. It was calculated that the value of Quality Adjusted Years of Life (QALY) was 45 years of life per capita earnings. The population of the study was composed of all the women of the city of Fortaleza. The data collection period was between January and April 2018. The data was analyzed using the Survival Table of the Brazilian Institute of Geography and Statistics The data were analyzed in Program R. The ethical aspects of Resolution 466/12. The Cost Ratio Incremental Effectiveness found was R$ 21.41. It was denoted that by implanting PROGYNE, women gain 45.02 years of life per capita. The estimated cost over time was R$ 1,085,019,025.05, representing a savings of R$ 447,677,508.32 for government costs. The clinical protocol has yielded positive results in terms of the cost of implementing new technologies to increase cervical cancer screening.